Effect of Crude Saponin of Korean Red Ginseng on High-Fat Diet-Induced Obesity in the Rat - Ji Hyun Kim; Dae Hyun Hahm; Deck Chun Yang; Jang Hyun Kim; Hye Jung Lee; Insop Shim (Elsevier, 2005)
The anti-obesity effects of crude saponin (CS) of Korean red ginseng (KRG) were investigated in the rat fed a high-fat (HF) diet. Male Sprague-Dawley (SD) rats became obese by feeding the HF diet over 5 weeks, while the control rats were fed a normal diet, and then both groups were treated with CS (200 mg/kg, i.p.) for 3 weeks. The body weight, food consumption, adipose tissues, and expression of appetite peptides such as leptin and neuropeptide Y (NPY) were investigated in rats fed normal and HF diet after treatment of CS. Administration of CS reduced body weight, food intake, and fat content in HF diet rats in a manner similar to those of the normal diet fed rats. The hypothalamic NPY expression and serum leptin level were reduced in HF diet rats after CS treatment. Our results suggest that CS may be useful in the treatment of obesity and related disorders as anti-obesity agents. Keywords:: crude saponin of Korean red ginseng, neuropeptide Y, leptin, hypothalamus, antiobesity